Determining the effect of dispersed aluminum particles on the functional properties of polymeric composites based on polyvinylidene fluoride - Lysenkov, Eduard; Klymenko, Leonid (Eastern-European Journal of Enterprise Technologies, 2021)
Polymeric materials that contain inorganic fillers demonstrate a unique set of physical properties due to the combination of matrix elasticity and filler strength. This paper reports determining the effect of dispersed aluminum particles on the properties of polyvinylidene fluoride-based materials. This study result is the fabrication of a series of composite materials using a piston extruder. Their functional characteristics have been explored using the methods of thermophysical and mechanical analysis, dilatometry, and acoustic spectroscopy. It was established that the introduction of dispersed aluminum particles leads to the loosening of the matrix, which may indicate the transition of macro macromolecules from the crystalline phase to the boundary layer around the filler. This feature of structure formation and the uniform distribution of filler particles ensured the improvement of the functional characteristics of the materials obtained. It has been shown that with an increase in the content of filler in the system to 5 % the thermal conductivity increases from 0.17 W/(m·K) to 1.55 W/(m·K). The introduction of the filler leads to an improvement in the heat resistance of the materials obtained, by 17 K. The increase in both melting point and destructiveness is explained by the formation of a more perfect polymer structure with a higher degree of crystallinity. An increase in the speed of ultrasound propagation was identified, by 67 %, as well as in the tensile strength, by 36 %, in the materials obtained, which can be explained by contributions from the filler, which has greater sound conductivity and mechanical strength than the polymer matrix. Such systems show the reinforcing effect of aluminum particles on the polymer matrix, so they could be used as structural materials with improved functional characteristics